Method for improving response speed of optical erasing liquid crystal display based on nanometer doping

By doping TiO2 nanoparticles in the photosensitive orientation layer and combining dynamic gradient light intensity irradiation technology, the problem of slow response speed of photo-driven liquid crystal display devices is solved, achieving faster response speed and lower energy consumption.

CN119689749APending Publication Date: 2025-03-25SHANTOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411818350.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Existing optically driven LCD display devices have slow response speed, affecting the performance of dynamic image display and fast information updates.

Method used

By doping TiO2 nanoparticles in the photosensitive orientation layer and combining dynamic gradient light intensity irradiation technology, the optical irradiation conditions are optimized to accelerate the orientation adjustment of liquid crystal molecules.

Benefits of technology

It significantly shortens the response time of LCD monitors, improves the response speed and performance stability of the monitor, while reducing energy consumption and equipment complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119689749A_ABST
    Figure CN119689749A_ABST
Patent Text Reader

Abstract

The invention relates to a method for improving the light response speed of a light erasing liquid crystal display device. The optical erasing liquid crystal display device includes a substrate, a photosensitive alignment layer, a non-photosensitive alignment layer, and a liquid crystal layer. The light response speed of the light erasing liquid crystal display device is increased by accurately controlling the doping proportion of the TiO2 nanoparticles in the photosensitive alignment layer. In addition, the dynamic gradient light intensity irradiation technology is combined to adjust the gradient change of the irradiation light intensity and the time duty ratio, and the response speed of the display device can be remarkably improved. Compared with the prior art, the method has the advantages that the optical erasing response speed is higher, the preparation process is simplified, and the cost is reduced. Therefore, the invention has important application prospect and commercial value in the technical field of optical erasing liquid crystal display.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of liquid crystal display, and in particular relates to a method for improving the response speed of a light-erasable liquid crystal display based on nano-doping. Background Art

[0002] ORW (Optically Rewritable) technology is an innovative liquid crystal display technology that controls the orientation of liquid crystal molecules through light drive to display and update information. Unlike traditional liquid crystal displays that rely on backlight and electric field drive, this technology does not require backlight and complex electric field systems, which significantly reduces energy consumption and manufacturing costs. The core of ORW technology lies in its optical erasing and rewriting capabilities. ORW device display uses reflected ambient light as a light source. By controlling the intensity, polarization properties and irradiation time of light, the molecular structure of the photosensitive orientation layer changes, thereby inducing changes in the orientation of liquid crystal molecules to achieve display effects. When linearly polarized light irradiates the ORW device, the arrangement direction of the photosensitive material molecules changes, thereby affecting the arrangement of adjacent liquid crystal molecules. This not only increases the update speed of the display, but also makes the device more energy-efficient and efficient. The ORW display device consists of two substrates with different orientation materials. One side is a light-stable polyimide (PI) orientation layer, and the other side is a photosensitive material azo dye (SD1) orientation layer. The state of the ORW display can be changed by redirecting the photosensitive layer with linear polarized light. This optical erasing method makes the display process green, environmentally friendly, energy-efficient and efficient. Although ORW technology has shown great potential, it still faces some challenges in practical applications, such as relatively slow optical erase response speed and rapid degradation of display performance. These issues need further research and improvement to give full play to the advantages of ORW technology.

[0003] An important influencing factor in liquid crystal display technology is the response time of the liquid crystal. Response time refers to the speed at which each pixel in the liquid crystal display device reacts to the input signal, that is, the time required for the pixel to change from dark to light or from light to dark. The shorter the response time, the better the performance of the display device when presenting dynamic images, and can effectively avoid the phenomenon of tail shadow dragging. ORW technology regulates the orientation of liquid crystal molecules through linear polarized light, without the need for backlight and electric field drive, to achieve a green, environmentally friendly, energy-saving and efficient display method. However, the light response characteristics of existing photosensitive orientation layer materials are not sensitive enough, resulting in a slow light erasure response speed. In actual display applications, especially in dynamic image display and rapid information update, fast response is crucial.

[0004] To improve the response speed of liquid crystal, in electrically driven liquid crystal display devices, common methods include optimizing the selection of liquid crystal materials and improving the driving circuit, such as using overvoltage driving technology to accelerate the response speed of liquid crystal molecules. Overvoltage driving technology applies a driving voltage higher or lower than the target state voltage to make the liquid crystal molecules adjust to the target state faster, thereby shortening the response time. The ORW device is a reflective liquid crystal display structure prepared by combining a light-controlled bistable azo SD1 molecular orientation layer and a non-photosensitive orientation layer; one orientation material is photoinert and maintains the original orientation direction unchanged on one substrate; the other substrate has an orientation layer that is photosensitive and can change its arrangement direction by exposing it to irradiated polarized light. The core of ORW technology lies in its light erasing capability. The ORW device display uses reflected ambient light as a light source without the need for an ITO layer. By controlling the intensity, polarization properties and irradiation time of the light, the molecular structure of the photosensitive orientation layer changes, thereby inducing changes in the orientation of the liquid crystal molecules to achieve the display effect. When linearly polarized light irradiates the ORW device, the arrangement direction of the photosensitive material molecules changes, thereby affecting the arrangement of adjacent liquid crystal molecules. Optical drive technology is mainly used in the field of optical erasure. It uses light energy to change material properties to achieve erasure and rewriting of information. This method is low-cost, simple to operate, environmentally friendly, and does not damage the material. In contrast, electric drive technology requires the use of conductive films, which makes it more expensive and more complicated to operate. There is also energy consumption and the risk of damage to the material during operation. Therefore, in terms of cost and ease of operation, optical drive technology has obvious advantages in the field of optical erasure.

[0005] Nano-doping technology is a method of changing the physical, chemical or optical properties of a material by introducing nano-scale doping substances into the material. Although this technology is widely used in the field of liquid crystals, especially in light-driven liquid crystal display devices, because it can improve performance and functionality, it also has some challenges. Since light driving relies on the absorption and energy conversion of light, which is different from the response mechanism of directly applying an electric field in electric driving, many doping systems that have good effects in electric driving, if directly applied to light-driven liquid crystal displays, will affect the response speed and efficiency of liquid crystal materials to light. The doping of nanoparticles may cause the response speed and efficiency of the light-driven system to be relatively slow or low efficiency. Therefore, how to obtain a doping system that can improve the response speed of the light-driven system has become the focus and difficulty of research in this field. Summary of the invention

[0006] The purpose of the present invention is to effectively accelerate the orientation adjustment of liquid crystal molecules by optimizing light irradiation conditions through nano-doping for light-driven display devices, thereby significantly shortening the response time of the display. Compared with the traditional electric drive method, this light-driven technology does not require complex circuits and high-voltage drive, which may reduce energy consumption and simplify equipment design and manufacturing processes. In the present invention, TiO2 nanoparticles have excellent photocatalytic and photoelectric properties, and doping into liquid crystal materials can enhance the response speed of liquid crystal to light. Nanoparticles can absorb light energy and quickly transfer it to liquid crystal molecules, thereby accelerating the reorientation and arrangement of molecules and solving the problem of slow response in light drive. In the light-driven system, by doping TiO2 and combining light intensity gradient control, the utilization efficiency of light energy can be effectively improved and the required total light intensity can be reduced. This can reduce the power consumption of the device while maintaining or improving the display performance.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0008] A photosensitive alignment layer for improving light erasing response speed comprises TiO2.

[0009] The present invention does not need to change the main structure of the light-erasable liquid crystal display device, and can improve the erasing speed of the light-erasable liquid crystal display only by doping TiO2 nanoparticles in the photosensitive alignment layer.

[0010] After research, it was surprisingly discovered that doping TiO2 nanoparticles in the photosensitive alignment layer can change the azimuthal anchoring energy of the SD1 molecules and thus improve the response speed. After doping with TiO2 nanoparticles, the azimuthal anchoring energy of the SD1 molecules in the photosensitive alignment layer changes under light. This means that the SD1 molecules can adjust their arrangement direction more quickly under the influence of light, reducing the hysteresis effect of the liquid crystal molecule response and significantly improving the response speed of the device. Compared with the traditional undoped structure, the addition of nanoparticles makes the interaction between the molecular layers more efficient, which helps to achieve fast and accurate display content updates.

[0011] Preferably, it also includes a photosensitizer; the TiO2 includes TiO2 nanoparticles with a size of 20 to 500 nm.

[0012] The present invention can significantly enhance the light response characteristics of liquid crystal by doping TiO2 nanoparticles into the orientation layer of liquid crystal molecules. Specifically, the addition of TiO2 nanoparticles can improve the orientation speed and response speed of liquid crystal molecules under light. This is because the small size and high specific surface area of ​​the nanoparticles enable them to absorb and transmit light energy more effectively, thereby accelerating the rearrangement and response process of liquid crystal molecules under the light field. In addition, nano-doping can also adjust the optical properties of liquid crystal materials, such as refractive index and transmittance, thereby improving the contrast and color performance of display devices. This technology can not only improve the performance of liquid crystal display devices, but also reduce their energy consumption and manufacturing costs because it reduces the dependence on complex driving devices, such as traditional backlight sources and complex electric field control systems.

[0013] Preferably, the photosensitizer includes an azo dye photosensitizer, and the particle size of the TiO2 includes 20 to 500 nm. More preferably, the photosensitizer includes an SD1 photosensitizer.

[0014] TiO2 nanoparticles can reduce the azimuthal anchoring energy of azo dye molecules, enhance the light response characteristics, and accelerate the rearrangement of liquid crystal molecules.

[0015] Preferably, in the photosensitive alignment layer, the doping concentration of TiO2 is in the range of 0.1 wt% to 0.9 wt%.

[0016] Preferably, in the photosensitive alignment layer, the doping concentration of TiO2 is 0.3wt%.

[0017] An application of the above-mentioned photosensitive alignment layer for improving the light erasing response speed is used to prepare a light erasable liquid crystal display.

[0018] A light-erasable liquid crystal display obtained by the above application.

[0019] The liquid crystal display device of the present invention adopts a new type of photosensitive orientation layer, which is composed of SD1 photosensitizer and TiO2 nanoparticles. By accurately controlling the doping ratio of TiO2 nanoparticles, the present invention can effectively adjust the photosensitivity of the orientation layer, reduce the azimuthal anchoring energy, thereby accelerating the rearrangement of liquid crystal molecules and achieving rapid response. By adopting a unique dynamic gradient light intensity irradiation technology, by accurately controlling the change gradient and duty cycle of the irradiation light intensity, efficient regulation of the orientation of liquid crystal molecules is achieved. Compared with traditional constant light intensity irradiation, the method of the present invention can significantly shorten the response time of liquid crystal molecules and improve the response speed of the display device. The preparation method of the present invention includes the steps of cleaning the substrate, spin coating the photosensitive orientation layer, curing, and encapsulating the liquid crystal box. In the process of spin coating the photosensitive orientation layer, the present invention pays special attention to controlling the concentration of the solution, the speed of spin coating and the temperature of curing to ensure the uniformity and photosensitivity of the orientation layer. The following are the main parts of the present invention:

[0020] S1: Structure of a light-erasable liquid crystal display device, such as Figure 1 :The device includes a substrate, a photosensitive alignment layer, a non-photosensitive alignment layer and a liquid crystal layer. Among them, the photosensitive alignment layer is composed of SD1 photosensitizer and TiO2 nanoparticles. By precisely controlling the doping ratio of TiO2 nanoparticles, the rearrangement of liquid crystal molecules is accelerated to achieve rapid response. The substrate uses high-transparency materials to ensure that light can efficiently penetrate and act on the liquid crystal layer. The non-photosensitive alignment layer uses stable polyimide (PI) material to provide good mechanical stability and chemical inertness, thereby ensuring the stable performance of the liquid crystal layer in various environments. The liquid crystal layer is sandwiched between the photosensitive alignment layer and the non-photosensitive alignment layer. Through precise process control, the liquid crystal molecules can be quickly and evenly rearranged under light, thereby achieving efficient optical erasing function.

[0021] S2: Nano-doping of the orientation layer: The present invention can significantly enhance the light response characteristics of liquid crystal by doping TiO2 nanoparticles into the photosensitive orientation layer. The addition of TiO2 nanoparticles improves the orientation speed and response speed of liquid crystal molecules under light. Nanoparticles have extremely high surface area and excellent optical properties, and can effectively absorb and transmit light energy, thereby accelerating the rearrangement process of liquid crystal molecules.

[0022] S3: Dynamic gradient control of irradiated light intensity: Dynamic gradient light intensity irradiation technology is used to effectively improve the orientation control of liquid crystal molecules by adjusting the gradient of light intensity change and duty cycle, and significantly improve the response speed and performance stability of the display device. Dynamic gradient light intensity irradiation technology includes the selection of light source and dynamic adjustment of light intensity. The light source adopts 450nm LED light source, and the light intensity is precisely adjusted through system control. The duty cycle is adjusted through the periodic change of light intensity, so that the liquid crystal molecules can quickly reach a stable state in a short time. This method not only improves the response speed of liquid crystal molecules, but also reduces the waste of light energy, making the entire system more energy-efficient.

[0023] S4: Preparation of ORW device. The preparation process is as follows Figure 2 :The preparation process of the present invention not only includes the optimization of material selection and spin coating conditions, but also includes the precise control of baking time. These comprehensive optimization measures jointly improve the performance of the orientation layer and the response speed of the display device. In terms of material selection, high-purity and high-stability SD1 photosensitizers and TiO2 nanoparticles are preferred to ensure the quality and performance of the photosensitive layer. The spin coating process makes the photosensitive layer uniform and dense by optimizing the spin coating speed, time and solution concentration. The precise control of baking time and temperature is to ensure the complete volatilization of the solvent in the photosensitive layer and the full curing of the material, and finally form a photosensitive orientation layer with excellent performance. The combination of these optimization measures makes the entire preparation process more efficient, and the optically erasable liquid crystal display device produced has higher performance.

[0024] A method for improving the response speed of a light-erasable liquid crystal display based on nano-doping includes doping TiO2 in a photosensitive alignment layer.

[0025] Preferably, the method further comprises adjusting the irradiation light intensity gradient; the light intensity gradient comprises 80% to 90%.

[0026] Preferably, the method further includes adjusting the irradiation duty cycle; the duty cycle includes 50%.

[0027] By doping the photosensitive alignment layer with TiO2 nanoparticles and changing the intensity of the irradiated light, the erasing speed of the light-erasable liquid crystal display can be improved. By doping the photosensitive alignment layer with TiO2 nanoparticles and changing the irradiation time duty cycle of the irradiated light, the erasing speed of the light-erasable liquid crystal display can be improved. By doping the photosensitive alignment layer with TiO2 nanoparticles and adjusting the gradient of the light intensity change and the duty cycle, the erasing speed of the light-erasable liquid crystal display can be improved.

[0028] When the doping concentration is within the range of 0.1wt%-0.9wt%, the response speed of the liquid crystal display is improved compared with the data of undoped constant light intensity, and it reaches the best at about 0.3wt%. At the optimal doping concentration, the response speed is improved the most under the conditions of 80%-90% gradient light intensity and 50% duty cycle; compared with the data of undoped constant light intensity, the improvement percentage is 35%. At the optimal doping concentration, the gradient light intensity after TiO2 nano doping can be improved by 10-30% compared with the data of constant light intensity of TiO2 nanoparticles doped alone. At the optimal doping concentration, the time duty cycle after TiO2 nano doping can be improved by 10-30% compared with the data of constant light intensity of TiO2 nanoparticles doped alone.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The present invention relates to a method for improving the light response speed of a light-erasable liquid crystal display device. The light-erasable liquid crystal display device includes a substrate, a photosensitive orientation layer, a non-photosensitive orientation layer and a liquid crystal layer. The present invention achieves the improvement of the light response speed of the light-erasable liquid crystal display device by accurately controlling the doping ratio of TiO2 nanoparticles in the photosensitive orientation layer. In addition, by combining the dynamic gradient light intensity irradiation technology to adjust the gradient change of the irradiation light intensity and the time duty cycle, the response speed of the display device can be significantly improved. Compared with the prior art, the present invention shows a faster light-erasable response speed, while simplifying the preparation process and reducing the cost. Therefore, the present invention has important application prospects and commercial value in the field of light-erasable liquid crystal display technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 is a schematic diagram of the structure of an ORW display device;

[0032] Figure 2 It is a schematic diagram of the preparation process of ORW device;

[0033] Figure 3 This is the optical path diagram for the ORW device monitoring response performance test;

[0034] Figure 4 This is the response time variation curve of the ORW device doped with different TiO2 concentrations;

[0035] Figure 5 This is a graph of the percentage increase in response time of the ORW device doped with TiO2 at different duty cycles corresponding to different light intensity gradient changes, where a is a duty cycle of 10%, b is a duty cycle of 30%, c is a duty cycle of 50%, d is a duty cycle of 70%, e is a duty cycle of 90%, and f is a duty cycle of 100%. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below in conjunction with specific embodiments.

[0037] Example 1

[0038] Only doped ORW preparation and testing

[0039] In order to achieve the purpose of the present invention, namely to provide a light-erasable liquid crystal display device with fast response speed and an optimized preparation method, the implementation steps of the present invention will be described in detail below with reference to the accompanying drawings.

[0040] Step 1) Substrate cleaning and preparation. A glass substrate with a size of 200 mm × 200 mm was selected as the starting material. Ultrasonic cleaning was performed in an ultrasonic cleaning machine using glass detergent and deionized water to remove dust and organic contaminants on the substrate. After cleaning, the substrate was placed in an oven at 120°C for drying, and then the glass substrate was placed in a UV cleaning machine for cleaning to remove moisture and enhance the cleanliness of the substrate surface.

[0041] Step 2) Preparation of photosensitive alignment agent solution. First, select SD1 photosensitizer as the main material of the alignment layer, use N,N-dimethylformamide (DMF) as the solvent, and prepare a 1% SD1 solution at a mass ratio of 1:99. TiO2 nanoparticles are used as doping materials and doped according to different weight ratios. In this experiment, 0.1wt%, 0.2wt%,..., 0.9wt%, 1wt% and undoped blank control groups are used to study the effects of different doping ratios on the response speed. Mix the SD1 solution with the TiO2 nanoparticles and use an ultrasonic oscillator for ultrasonic treatment to ensure that the TiO2 nanoparticles are evenly dispersed in the SD1 solution. Centrifuge the treated mixed solution to remove possible agglomerated particles and improve the uniformity and stability of the solution.

[0042] Step 3) Coating and curing of the orientation layer. Use a spin coater to evenly coat the SD1-TiO2 mixed solution on a pre-cleaned glass substrate, set the rotation speed to 3000rpm, and set the coating time to 50 seconds. Place the coated glass substrate in a heating table, set the temperature to 140°C, and heat for 15 minutes to cure the photosensitive orientation layer. At the same time, the non-photosensitive material polyimide (PI) solution is also spin-coated on another glass substrate. At this time, the spin coating step is divided into two steps. The first step sets the rotation speed to 1000rpm for 15 seconds, and the second part sets the rotation speed to 3000rpm for 40 seconds. Then preheat the substrate on the heating table for 10 minutes, then heat it at 220 degrees Celsius for 60 minutes. After the film is cured, cool it to room temperature for use.

[0043] Step 4) Preparation of liquid crystal cell. Figure 2 As shown, a friction orientation machine is used to perform friction orientation treatment on the cured PI layer to ensure uniform arrangement of the liquid crystal molecules on the orientation layer. Spacer particles are evenly sprayed on the substrate after the orientation treatment, and the diameter of the spacer particles is 10 microns to form the spacing layer of the liquid crystal box. It is aligned and bonded with the substrate coated with the photosensitive orientation layer to form a liquid crystal box. The box structure is shown in FIG. Figure 1 As shown. Inject a proper amount of liquid crystal material on one side of the liquid crystal box and use capillary action to fill the entire liquid crystal box. Use vacuum compression technology to seal the edge of the liquid crystal box to ensure the sealing and stability of the liquid crystal box.

[0044] Step 5) Measurement of the response characteristics of the liquid crystal in the light-erasable liquid crystal display. Figure 3The liquid crystal response characteristic measurement system shown in the figure includes laser, ultraviolet irradiation light source, polarizer, motor rotating platform, filter, detector and oscilloscope and other main components. A helium-neon laser with a wavelength of 632.8nm is used as the detection light source, which is responsible for detecting the optical signal changed by the change of the transmittance of the ORW device. After the outgoing light passes through the second polarizer, it is received by the photodetector and converted into an electrical signal, and finally displayed on the oscilloscope to observe the liquid crystal response characteristics. A liquid crystal box fixing frame is installed on the motor rotating platform, and the platform can accurately adjust the rotation angle of the liquid crystal box within the range of ±90 degrees to erase and write the liquid crystal box.

[0045] Step 6) In the erase test, the light erase response time is defined as: when the ORW sample is illuminated by a polarized light source, the SD1 molecules drive the liquid crystal molecules to rotate, and the time it takes for the detector 1 to receive the ORW light transmittance changing from 0% to 90%, which is defined as the response time of the ORW liquid crystal device.

[0046] By doping TiO2 nanoparticles in the photosensitive alignment agent SD1, the response speed of ORW electronic paper is significantly improved. In particular, the response speed is the fastest at a doping concentration of 0.3%, and the erase time reaches 20s. Compared with the ORW display sample with constant light intensity without nanoparticles, its overall response speed is improved by about 20%. The test results are as follows Figure 4 However, when the doping concentration of TiO2 nanoparticles exceeds this optimal ratio, the response speed slows down. This may be because the aggregation of nanoparticles at too high a concentration increases the resistance to the rotation of liquid crystal molecules.

[0047] Example 2

[0048] Preparation and testing of ORW with doping gradient and time duty cycle

[0049] Step 1) Substrate cleaning and preparation. A glass substrate with a size of 200 mm × 200 mm was selected as the starting material. Ultrasonic cleaning was performed in an ultrasonic cleaning machine using glass detergent and deionized water to remove dust and organic contaminants on the substrate. After cleaning, the substrate was placed in an oven at 120°C for drying, and then the glass substrate was placed in a UV cleaning machine for cleaning to remove moisture and enhance the cleanliness of the substrate surface.

[0050] Step 2) Preparation of photosensitive alignment agent solution. First, select SD1 photosensitizer as the main material of the alignment layer, use N,N-dimethylformamide (DMF) as the solvent, and prepare a 1% SD1 solution at a mass ratio of 1:99. TiO2 nanoparticles are used as doping materials and doped according to different weight ratios. In this experiment, 0.1wt%, 0.2wt%,..., 0.9wt%, 1wt% and undoped blank control groups are used to study the effects of different doping ratios on the response speed. Mix the SD1 solution with the TiO2 nanoparticles and use an ultrasonic oscillator for ultrasonic treatment to ensure that the TiO2 nanoparticles are evenly dispersed in the SD1 solution. Centrifuge the treated mixed solution to remove possible agglomerated particles and improve the uniformity and stability of the solution.

[0051] Step 3) Coating and curing of the orientation layer. Use a spin coater to evenly coat the SD1-TiO2 mixed solution on a pre-cleaned glass substrate, set the rotation speed to 3000rpm, and set the coating time to 50 seconds. Place the coated glass substrate in a heating table, set the temperature to 140°C, and heat for 15 minutes to cure the photosensitive orientation layer. At the same time, the non-photosensitive material polyimide (PI) solution is also spin-coated on another glass substrate. At this time, the spin coating step is divided into two steps. The first step sets the rotation speed to 1000rpm for 15 seconds, and the second part sets the rotation speed to 3000rpm for 40 seconds. Then preheat the substrate on the heating table for 10 minutes, then heat it at 220 degrees Celsius for 60 minutes. After the film is cured, cool it to room temperature for use.

[0052] Step 4) Preparation of liquid crystal cell. Figure 2 The PI layer after curing is subjected to rubbing orientation treatment by a rubbing orientation machine to ensure uniform arrangement of the liquid crystal molecules on the orientation layer. Spacer particles are evenly sprayed on the substrate after orientation treatment, and the diameter of the spacer particles is 10 microns to form the spacer layer of the liquid crystal box. It is aligned and bonded with the substrate coated with the photosensitive orientation layer to form a liquid crystal box. The box structure is shown in FIG. Figure 1 As shown. Inject a proper amount of liquid crystal material on one side of the liquid crystal box and use capillary action to fill the entire liquid crystal box. Use vacuum compression technology to seal the edge of the liquid crystal box to ensure the sealing and stability of the liquid crystal box.

[0053] Step 5) Measurement of the response characteristics of the liquid crystal in the light-erasable liquid crystal display. Figure 3The liquid crystal response characteristic measurement system shown in the figure includes laser, ultraviolet irradiation light source, polarizer, motor rotating platform, filter, detector and oscilloscope and other main components. A helium-neon laser with a wavelength of 632.8nm is used as the detection light source, which is responsible for detecting the optical signal changed by the change of the transmittance of the ORW device. After the outgoing light passes through the second polarizer, it is received by the photodetector and converted into an electrical signal, and finally displayed on the oscilloscope to observe the liquid crystal response characteristics. A liquid crystal box fixing frame is installed on the motor rotating platform, and the platform can accurately adjust the rotation angle of the liquid crystal box within the range of ±90 degrees to erase and write the liquid crystal box.

[0054] Step 6) Different from the implementation example 1, here, the response speed of the prepared ORW device is tested by combining a dynamic gradient light intensity irradiation system. The specific dynamic gradient light intensity irradiation system is: the light power of 450nm wavelength is 20mW / cm 2 An LED is used as a linearly polarized light source, and a polarizer is provided to ensure that the polarization direction of the light is the same as that of the photosensitive orientation layer of the liquid crystal box. A precise light intensity controller is used, which is capable of adjusting the intensity of the light source from 0% to 100% to achieve the desired light intensity gradient. Based on the optimal doping concentration of 0.3wt% in the specific implementation case 1, the light intensity is adjusted and controlled to change from 10%, 20%, 30%... to 90%, respectively. Based on the condition of the light intensity gradient change, the range of its gradient light intensity change is changed, that is, the ratio of the light intensity gradient change time to the entire response time of the ORW liquid crystal device. Under a series of duty cycle conditions of 10%, 30%, 50%, 70%, 90%, and 100%, the response time of the ORW liquid crystal device under different light intensity gradients and time duty cycles is tested.

[0055] Step 7) In the analysis of the erase test results, the light erase response time is defined as: when the ORW sample is illuminated by a polarized light source, the SD1 molecules drive the liquid crystal molecules to rotate, and the time it takes for the detector 1 to receive the ORW light transmittance changing from 0% to 90%, which is defined as the response time of the ORW liquid crystal device.

[0056] The test results are as follows Figure 5 As shown in af, the “-” in the figure represents the percentage of response time growth, which is the display speed of the ORW sample doped with TiO2 nanoparticles but not dynamically irradiated. If it is a negative number, it means that the response speed is shortened, which means that the response speed has been improved; “+” represents that the percentage of response time growth is a positive number, that is, the response time becomes longer, which means that the response speed is reduced. Figure 5It can be seen that 80%-90% gradient light intensity and 50% duty cycle are the best conditions, and the response speed is increased to 17s, which is 37% higher than that of the undoped and non-dynamically irradiated ORW samples. Overall, under the same conditions, the response speed of the undoped TiO2 ORW device is better than that of the doped TiO2 device. Under the superposition of the optimized conditions of doping TiO2 nanoparticles, changing the irradiation light intensity, and changing the irradiation light time duty cycle, the response speed of the ORW device can be improved to the best.

[0057] Example 3

[0058] Preparation and testing of ORW with doping-light variation

[0059] Step 1) Substrate cleaning and preparation. A glass substrate with a size of 200 mm × 200 mm was selected as the starting material. Ultrasonic cleaning was performed in an ultrasonic cleaning machine using glass detergent and deionized water to remove dust and organic contaminants on the substrate. After cleaning, the substrate was placed in an oven at 120°C for drying, and then the glass substrate was placed in a UV cleaning machine for cleaning to remove moisture and enhance the cleanliness of the substrate surface.

[0060] Step 2) Preparation of photosensitive alignment agent solution. First, select SD1 photosensitizer as the main material of the alignment layer, use N,N-dimethylformamide (DMF) as the solvent, and prepare a 1% SD1 solution at a mass ratio of 1:99. TiO2 nanoparticles are used as doping materials and doped according to different weight ratios. In this experiment, 0.1wt%, 0.2wt%,..., 0.9wt%, 1wt% and undoped blank control groups are used to study the effects of different doping ratios on the response speed. Mix the SD1 solution with the TiO2 nanoparticles and use an ultrasonic oscillator for ultrasonic treatment to ensure that the TiO2 nanoparticles are evenly dispersed in the SD1 solution. Centrifuge the treated mixed solution to remove possible agglomerated particles and improve the uniformity and stability of the solution.

[0061] Step 3) Coating and curing of the orientation layer. Use a spin coater to evenly coat the SD1-TiO2 mixed solution on a pre-cleaned glass substrate, set the rotation speed to 3000rpm, and set the coating time to 50 seconds. Place the coated glass substrate in a heating table, set the temperature to 140°C, and heat for 15 minutes to cure the photosensitive orientation layer. At the same time, the non-photosensitive material polyimide (PI) solution is also spin-coated on another glass substrate. At this time, the spin coating step is divided into two steps. The first step sets the rotation speed to 1000rpm for 15 seconds, and the second part sets the rotation speed to 3000rpm for 40 seconds. Then preheat the substrate on the heating table for 10 minutes, then heat it at 220 degrees Celsius for 60 minutes. After the film is cured, cool it to room temperature for use.

[0062] Step 4) Preparation of liquid crystal cell. Figure 2 The PI layer after curing is subjected to rubbing orientation treatment by a rubbing orientation machine to ensure uniform arrangement of the liquid crystal molecules on the orientation layer. Spacer particles are evenly sprayed on the substrate after orientation treatment, and the diameter of the spacer particles is 10 microns to form the spacer layer of the liquid crystal box. It is aligned and bonded with the substrate coated with the photosensitive orientation layer to form a liquid crystal box. The box structure is shown in FIG. Figure 1 As shown. Inject a proper amount of liquid crystal material on one side of the liquid crystal box and use capillary action to fill the entire liquid crystal box. Use vacuum compression technology to seal the edge of the liquid crystal box to ensure the sealing and stability of the liquid crystal box.

[0063] Step 5) Measurement of the response characteristics of the liquid crystal in the light-erasable liquid crystal display. Figure 3 The liquid crystal response characteristic measurement system shown in the figure includes laser, ultraviolet irradiation light source, polarizer, motor rotating platform, filter, detector and oscilloscope and other main components. A helium-neon laser with a wavelength of 632.8nm is used as the detection light source, which is responsible for detecting the optical signal changed by the change of the transmittance of the ORW device. After the outgoing light passes through the second polarizer, it is received by the photodetector and converted into an electrical signal, and finally displayed on the oscilloscope to observe the liquid crystal response characteristics. A liquid crystal box fixing frame is installed on the motor rotating platform, and the platform can accurately adjust the rotation angle of the liquid crystal box within the range of ±90 degrees to erase and write the liquid crystal box.

[0064] Step 6) According to implementation example 2, the response speed of the prepared ORW device is tested by combining a dynamic gradient light intensity irradiation system. The specific dynamic gradient light intensity irradiation system is: the light power at a wavelength of 450nm is 20mW / cm 2 An LED is used as a linearly polarized light source, and a polarizer is provided to ensure that the polarization direction of the light is the same as that of the photosensitive orientation layer of the liquid crystal box. A precise light intensity controller is used, which is capable of adjusting the intensity of the light source from 0% to 100% to achieve the desired light intensity gradient. Based on the optimal doping concentration of 0.3wt% in the specific implementation case 1, the light intensity is adjusted and controlled to change from 10%, 20%, 30%... to 90%, respectively. Based on the condition of the light intensity gradient change, the range of its gradient light intensity change is changed, that is, the ratio of the light intensity gradient change time to the entire response time of the ORW liquid crystal device. Under a series of duty cycle conditions of 10%, 30%, 50%, 70%, 90%, and 100%, the response time of the ORW liquid crystal device under different light intensity gradients and time duty cycles is tested.

[0065] According to the test results Figure 5 The data are organized into Table 1. The data in the table represent the percentage increase in the response speed of the ORW device without nanoparticles under constant light intensity.

[0066] Table 1

[0067]

[0068] From the results we can see that:

[0069] 1) Under the same duty cycle conditions, by doping TiO2 nanoparticles in the photosensitive alignment layer and changing the light intensity gradient of the irradiated light, the ORW device prepared after doping can achieve an improvement in the erasing speed of the light-erasable liquid crystal display. It can be found from Table 1 that the light response time of the ORW device will gradually shorten with the increase of the starting light intensity in the gradient interval. Compared with the response time under the constant 90% light intensity irradiation of the undoped device, the response speed of the ORW device under all gradient light intensity irradiation conditions has become faster, and the fastest improvement is achieved under the gradient of 80%-90%, which can be increased by about 20%-30%;

[0070] 2) Under the same light gradient conditions, by doping TiO2 nanoparticles in the photosensitive alignment layer and changing the irradiation time duty cycle of the irradiated light, the ORW device made after doping can achieve an increase in the erasing speed of the light-erasable liquid crystal display. The overall response speed is improved compared to the undoped 90% constant light intensity irradiation, and the fastest improvement is when the duty cycle is 50%, which can be increased by about 20%-30%.

[0071] Example 4

[0072] Preparation and testing of ORW with doping-gradient variation

[0073] Step 1) Substrate cleaning and preparation. A glass substrate with a size of 200 mm × 200 mm was selected as the starting material. Ultrasonic cleaning was performed in an ultrasonic cleaning machine using glass detergent and deionized water to remove dust and organic contaminants on the substrate. After cleaning, the substrate was placed in an oven at 120°C for drying, and then the glass substrate was placed in a UV cleaning machine for cleaning to remove moisture and enhance the cleanliness of the substrate surface.

[0074] Step 2) Preparation of photosensitive alignment agent solution. First, select SD1 photosensitizer as the main material of the alignment layer, use N,N-dimethylformamide (DMF) as the solvent, and prepare a 1% SD1 solution at a mass ratio of 1:99. TiO2 nanoparticles are used as doping materials and doped according to different weight ratios. In this experiment, 0.1wt%, 0.2wt%,..., 0.9wt%, 1wt% and undoped blank control groups are used to study the effects of different doping ratios on the response speed. Mix the SD1 solution with the TiO2 nanoparticles and use an ultrasonic oscillator for ultrasonic treatment to ensure that the TiO2 nanoparticles are evenly dispersed in the SD1 solution. Centrifuge the treated mixed solution to remove possible agglomerated particles and improve the uniformity and stability of the solution.

[0075] Step 3) Coating and curing of the orientation layer. Use a spin coater to evenly coat the SD1-TiO2 mixed solution on a pre-cleaned glass substrate, set the rotation speed to 3000rpm, and set the coating time to 50 seconds. Place the coated glass substrate in a heating table, set the temperature to 140°C, and heat for 15 minutes to cure the photosensitive orientation layer. At the same time, the non-photosensitive material polyimide (PI) solution is also spin-coated on another glass substrate. At this time, the spin coating step is divided into two steps. The first step sets the rotation speed to 1000rpm for 15 seconds, and the second part sets the rotation speed to 3000rpm for 40 seconds. Then preheat the substrate on the heating table for 10 minutes, then heat it at 220 degrees Celsius for 60 minutes. After the film is cured, cool it to room temperature for use.

[0076] Step 4) Preparation of liquid crystal cell. Figure 2 The PI layer after curing is subjected to rubbing orientation treatment by a rubbing orientation machine to ensure uniform arrangement of the liquid crystal molecules on the orientation layer. Spacer particles are evenly sprayed on the substrate after orientation treatment, and the diameter of the spacer particles is 10 microns to form the spacer layer of the liquid crystal box. It is aligned and bonded with the substrate coated with the photosensitive orientation layer to form a liquid crystal box. The box structure is shown in FIG. Figure 1 As shown. Inject a proper amount of liquid crystal material on one side of the liquid crystal box and use capillary action to fill the entire liquid crystal box. Use vacuum compression technology to seal the edge of the liquid crystal box to ensure the sealing and stability of the liquid crystal box.

[0077] Step 5) Measurement of the response characteristics of the liquid crystal in the light-erasable liquid crystal display. Figure 3 The liquid crystal response characteristic measurement system shown in the figure includes laser, ultraviolet irradiation light source, polarizer, motor rotating platform, filter, detector and oscilloscope and other main components. A helium-neon laser with a wavelength of 632.8nm is used as the detection light source, which is responsible for detecting the optical signal changed by the change of the transmittance of the ORW device. After the outgoing light passes through the second polarizer, it is received by the photodetector and converted into an electrical signal, and finally displayed on the oscilloscope to observe the liquid crystal response characteristics. A liquid crystal box fixing frame is installed on the motor rotating platform, and the platform can accurately adjust the rotation angle of the liquid crystal box within the range of ±90 degrees to erase and write the liquid crystal box.

[0078] Step 6) According to implementation example 2, the response speed of the prepared ORW device is tested by combining a dynamic gradient light intensity irradiation system. The specific dynamic gradient light intensity irradiation system is: the light power at a wavelength of 450nm is 20mW / cm 2An LED is used as a linearly polarized light source, and a polarizer is provided to ensure that the polarization direction of the light is the same as that of the photosensitive orientation layer of the liquid crystal box. A precise light intensity controller is used, which is capable of adjusting the intensity of the light source from 0% to 100% to achieve the desired light intensity gradient. Based on the optimal doping concentration of 0.3wt% in the specific implementation case 1, the light intensity is adjusted and controlled to change from 10%, 20%, 30%... to 90%, respectively. Based on the condition of the light intensity gradient change, the range of its gradient light intensity change is changed, that is, the ratio of the light intensity gradient change time to the entire response time of the ORW liquid crystal device. Under a series of duty cycle conditions of 10%, 30%, 50%, 70%, 90%, and 100%, the response time of the ORW liquid crystal device under different light intensity gradients and time duty cycles is tested.

[0079] Effect Example 1

[0080] According to the data of specific cases 1, 2, and 3, they are organized into Table 2, comparing the results of undoped TiO2 at constant light intensity, doped TiO2 at constant light intensity, and doped TiO2 with changing light intensity gradient and duty cycle.

[0081] Table 2

[0082]

[0083] In summary, it can be seen from the above test results:

[0084] First, when the photosensitive alignment layer is doped with TiO2 nanoparticles and under dynamic irradiation conditions, the erasing speed of the light-erasable liquid crystal display can be improved, which can be increased by up to 30% compared with undoped TiO2 nanoparticles under constant light intensity conditions.

[0085] Second, under the same irradiation duty cycle, the erasing speed of the light-erasable liquid crystal display can be improved by doping TiO2 nanoparticles in the photosensitive alignment layer, which can be increased by up to 30% compared with constant light intensity doping.

[0086] Third, by doping TiO2 nanoparticles and adjusting the light intensity gradient and duty cycle, the erasing speed of the light-erasable liquid crystal display can be improved. Compared with the undoped constant-intensity ORW sample, the response speed can be increased by up to 37%.

[0087] The above disclosure is only the preferred embodiment of the present invention, which cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.

Claims

1. A photosensitive alignment layer for improving the light erasing response speed, characterized in that: Including TiO2.

2. The photosensitive alignment layer for improving the light erasing response speed according to claim 1, characterized in that: It also includes a photosensitizer; and the TiO2 includes TiO2 nanoparticles.

3. The photosensitive alignment layer for improving the light erasing response speed according to claim 1, characterized in that: The photosensitizer includes an azo dye photosensitizer; the particle size of the TiO2 includes 20 to 500 nm.

4. The photosensitive alignment layer for improving the light erasing response speed according to claim 1, characterized in that: In the photosensitive alignment layer, the doping concentration of TiO2 is in the range of 0.1 wt% to 0.9 wt%.

5. The photosensitive alignment layer for improving the light erasing response speed according to claim 1, characterized in that: In the photosensitive alignment layer, the doping concentration of TiO2 is 0.3wt%.

6. An application of the photosensitive alignment layer for improving the light erasing response speed as claimed in claim 1, characterized in that: Used to prepare optically erasable liquid crystal displays.

7. A light-erasable liquid crystal display obtained by the application as claimed in claim 6.

8. A method for improving the response speed of a light-erasable liquid crystal display based on nano-doping, characterized in that: Including doping TiO2 in the photosensitive alignment layer.

9. The method according to claim 8, characterized in that The method also includes adjusting the irradiation light intensity gradient; the light intensity gradient includes 80% to 90%.

10. The method according to claim 8, characterized in that: Also included is adjusting the irradiation duty cycle; the duty cycle includes 50%.

Citation Information

Patent Citations

  • Device for optimizing performance of liquid crystal light-driven display sample and light adjusting method

    CN114859583A

  • Micro-domain structure photosensitive liquid crystal composite film based on orientation regulation and control and preparation method of micro-domain structure photosensitive liquid crystal composite film

    CN118963017A